Diagnosis and Management of Polycystic Ovary Syndrome: A Survey of Physicians from the Middle East and Africa - Beshyah, Salem A.; Bashir, Mohammed; Ekhzaimy, Aishah; Mansour, Abbas Ali; Mustafa, Huda E.; Elbarbary, Nancy; Ghazeeri, Ghina; Abdel Rahim, Hisham Mohamed; Abdelmannan, Dima K. (Journal of Diabetes and Endocrine Practice, 2022)
Background Studies from several regions examined the approach to diagnosing and managing polycystic ovary syndrome (PCOS). Limited data are available from the Middle East and Africa (MEA).Objective The aim of this study was to understand the practice pattern for diagnosing and managing PCOS by relevant specialists across the MEA region.Methods We used an online survey consisting of an established questionnaire. The questionnaire consisted of 25 questions grouped to capture information on (a) the characteristics of the respondents, (b) patients with PCOS seen by respondents, (c) the diagnostic criteria, (d) biochemical parameters for differential diagnosis of hyperandrogenism, (e) long-term concerns, and, finally (f) management choices.Results A total of 190 questionnaires were available for final analysis; 73.7% of the respondents were senior physicians; 59.5% and 17.4% were endocrinologists and gynecologists, respectively. Menstrual irregularity was the most frequent criterion used for the diagnosis of PCOS (90.5%), followed by hirsutism (75.7%), and biochemical hyperandrogenism (71.4%). Dehydroepiandrosterone was the most frequent biochemical parameter used for the differential diagnosis of hyperandrogenism (52.4%) followed by total testosterone (45.4%). Obesity and type 2 diabetes mellitus were the principal long-term concerns for PCOS (45.1%), followed by infertility (29.9%). Metformin was the most commonly prescribed treatment (43.8%), followed by lifestyle modification (27.0%), and oral contraceptives (18.9%). Infertility treatments include metformin alone, clomiphene citrate alone, or their combination prescribed by 23.1, 9.9, or 52.7%, respectively, whereas only 3.8% contemplated ovulation induction. Some differences and similarities were observed in previous studies, including gynecologists and endocrinologists.Conclusions This survey provides a baseline for the perspective in diagnosing and treating PCOS in the MEA region. Some deviation is observed from mainline recommended practices. More education on PCOS diagnostic criteria and treatment of PCOS is needed in line with the recently published evidence international guideline.
Keywords: polycystic ovary syndrome; clinical practices; metabolic syndrome; antiandrogens; MENA region; Africa